Street Traders and “Good Officers”: Crackdowns as a Relational Form of Urban Governance in Nairobi - Brigitte Dragsted-Mutengwa (Articulo: Journal of Urban Research, 2018)
In central Nairobi, crackdowns on illegal street trading by officers from the local authorities are a daily occurrence. Based on an ethnographic study of encounters between street traders and officers during crackdown operations in and around the Nairobi CBD, this article argues that crackdowns work as a platform for exchanges and thereby for the formation of social relationships. It explores how such relationships are formed and maintained during crackdowns, and how a range of urban actors has interests invested in them. The article contributes to regional literature on street trading by proposing a view of urban governance as emerging through everyday interactions and relations between urban actors. Furthermore, the article contributes to scholarship on relational urban governance by exemplifying how anthropological notions of exchange provide an analytical avenue through which such everyday interactions and relations can be explored.